The cultural politics of food and eating : a reader. - Watson, James L.; Caldwell, Melissa L. (Blackwell readers in anthropology, 2009)
"The Cultural Politics of Food and Eating is a collection of readings that uses the study of food as a vehicle for addressing broad themes that are emerging in social anthropology: globalization, capitalism, market economies, and consumption practices." "The Cultural Politics of Food and Eating offers an ethnographically informed perspective on the ways in which people use food to make sense of life in an increasingly interconnected world. It includes studies from eleven countries across five continents on such hot topics as sushi, fast food, gourmet foods, and food scares and contamination." -- Présentation de l'éditeur.